2020
DOI: 10.12669/pjms.36.5.1938
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ultrasound placental diameter & thickness with gestational age

Abstract: Background & Objectives: Estimation of fetal maturity is common in obstetric practice especially when the women do not keep accurate menstrual records. An accurate establishment of expected date of delivery is fundamental to the management of both high risk and normal pregnancies. The objective of this study was to determine the placental diameter (PD), placental thickness (PT) and to establish a correlation between PD, PT and gestational age. Methods: This is an observational cross-sectional study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The study found a cut off placental thickness more than 36.3 mm can be used to differentiate between term and preterm pregnancy. Similar findings were also reported by the authors such as Erkamp et al and Njeze et al 13,14 IN our study we found that that there was a Strong positive correlation between placental thickness and gestational age from 12 weeks to 38 weeks of gestation after which there was negative correlation between placental thickness and gestational age. Karthikeyan et al conducted a cross sectional study to estimate the (Placental thickness) PT and at investigating the relationship between PT and the foetal growth parameters in normal singleton pregnancies.…”
Section: Discussionsupporting
confidence: 92%
“…The study found a cut off placental thickness more than 36.3 mm can be used to differentiate between term and preterm pregnancy. Similar findings were also reported by the authors such as Erkamp et al and Njeze et al 13,14 IN our study we found that that there was a Strong positive correlation between placental thickness and gestational age from 12 weeks to 38 weeks of gestation after which there was negative correlation between placental thickness and gestational age. Karthikeyan et al conducted a cross sectional study to estimate the (Placental thickness) PT and at investigating the relationship between PT and the foetal growth parameters in normal singleton pregnancies.…”
Section: Discussionsupporting
confidence: 92%
“…Various studies have shown that there is a positive correlation between increasing gestational age and PT. 13 Karthikeyan et al, conducted a study to analyze the relationship between PT and the fetal growth parameters in normal singleton pregnancies. The authors included 211 pregnant women in this cross-sectional prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that the placental thickness increases gradually with the advancing gestational age. Njeze et al, 16 concluded that the placental thickness is a good predictor for estimating gestational age. In our study the significant positive correlation of PT was noted with gestational age with Pearson Correlation of 0.985 and p-value of 0.001 and with all other ultrasonographic fetal growth parameters i.e., BPD, FL, AC, HC with Pearson correlation of 0.988, 0.987, 0.991 and 0.988 and p-values of 0.001, 0.001, 0.001 and 0.001 respectively.…”
Section: Discussionmentioning
confidence: 99%